Construction of inclusive education imaginaries from the class of physical education (Impetus, 2021)
This research - article show the understanding of social imaginaries, built on inclusive education through the physical education class in both hearing and non-hearing students of the José Celestino Mutis School in Fusagasugá – Cundinamarca. The research was developed under a historical hermeneutical paradigm, with qualitative approach and phenomenological method; it can contribute to the exploration of realities in different contexts like primary, secondary or university level. From two categories of educational inclusion analysis and Physical Education and social Imaginary, six subcategories emerge, and it is interpreted that addressing the subject of the discipline, contributes to aspects such as new ways of generating knowledge, educational links, recognition of diversity, conformation of new friendship groups, interactive strategies and teamwork, where students indirectly learn new ways of communication, support and explain between theirs, as well as contributing to socialization, participation, and cooperation not only with their peers but with teachers also. In that way, the school is the propitious scenario in different levels to learn, relearn and modify social imaginaries for a better and timelier coexistence.